2014
DOI: 10.1038/onc.2014.146
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of eIF4E promotes EMT and metastasis via translational control of SNAIL and MMP-3

Abstract: The progression of cancers from primary tumors to invasive and metastatic stages accounts for the overwhelming majority of cancer deaths. Understanding the molecular events which promote metastasis is thus critical in the clinic. Translational control is emerging as an important factor in tumorigenesis. The mRNA cap-binding protein eIF4E is an oncoprotein that plays an important role in cancer initiation and progression. eIF4E must be phosphorylated to promote tumor development. However, the role of eIF4E phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
244
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(268 citation statements)
references
References 76 publications
13
244
0
3
Order By: Relevance
“…58 Although phosphorylation of eIF4E does not have a major impact on global translation rates, it was found to stimulate the translation of a subset of mRNAs encoding proteins involved in survival (e.g., Mcl1) 59 and tumor invasion (e.g.,, Snail, MMP-3). 60,61 Translational regulation of Snail and MMP-3 mRNAs was found to promote epithelial-to-mesenchymal transition (EMT), pointing to a role for eIF4E phosphorylation in cancer metastasis. 60 However, the precise mechanisms by which eIF4E phosphorylation affects the translation of these transcripts remain to be determined.…”
Section: Translational Regulation Of "Eif4e-sensitive" Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Although phosphorylation of eIF4E does not have a major impact on global translation rates, it was found to stimulate the translation of a subset of mRNAs encoding proteins involved in survival (e.g., Mcl1) 59 and tumor invasion (e.g.,, Snail, MMP-3). 60,61 Translational regulation of Snail and MMP-3 mRNAs was found to promote epithelial-to-mesenchymal transition (EMT), pointing to a role for eIF4E phosphorylation in cancer metastasis. 60 However, the precise mechanisms by which eIF4E phosphorylation affects the translation of these transcripts remain to be determined.…”
Section: Translational Regulation Of "Eif4e-sensitive" Transcriptsmentioning
confidence: 99%
“…60,61 Translational regulation of Snail and MMP-3 mRNAs was found to promote epithelial-to-mesenchymal transition (EMT), pointing to a role for eIF4E phosphorylation in cancer metastasis. 60 However, the precise mechanisms by which eIF4E phosphorylation affects the translation of these transcripts remain to be determined.…”
Section: Translational Regulation Of "Eif4e-sensitive" Transcriptsmentioning
confidence: 99%
“…MNK1 and MNK2 are serine/threonine protein kinases responsible for the phosphorylation of S209 on eIF4E [25]. The phosphorylation of eIF4E correlates with the increase in mesenchymal markers such as N-cadherin, fibronectin and vimentin, along with the acquisition of invasive properties [26].…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…Of note, although it may possess an IRES, SNAI1 translation is not maintained at the same level in A549 cells that harbor the eIF3e-targeting shRNA as in A549 cells that harbor the nontargeting shRNA. As it was recently shown that eIF4E phosphorylation is necessary for SNAI1 translation (37) and that eIF3e is necessary for eIF4E phosphorylation through the recruitment of MNK1 (38), we tested whether a decrease in eIF3e levels leads to a decrease in eIF4E phosphorylation. We examined the phosphorylation status of eIF4E and found that it is less phosphorylated in cells that have reduced eIF3e expression ( Supplementary Fig.…”
Section: Decreased Eif3e Expression Favors Cap-independent Translatiomentioning
confidence: 99%